In Vivo Reflectance Confocal Microscopy in General Dermatology: How to Choose the Right Indication - Franceschini, Chiara; Persechino, Flavia; Ardigò, Marco (Dermatology Practical & Conceptual, 2020)
Reflectance confocal microscopy (RCM) is a high-resolution, noninvasive imaging technique being increasingly used as an aid to diagnosis in the dermatology setting. RCM is applied in the diagnosis of both melanoma and nonmelanoma skin tumors, but also in the interpretation and management of inflammatory skin diseases. Two different devices with different designs for specific indications are available in the market: a static and a handheld probe. Several clinical presentations of the lesion could affect the examination, such as the presence of ulceration or hyperkeratosis; moreover, the anatomical site can drive the probe selection as well as the effective indication to RCM examination. In this review article, indications for the use of RCM are described in detail with a schematic approach for practical purposes.